A triangulation approach in analyzing creative economy: Evidence from Wonogiri regency - Prasetyani, Dwi; Sumardi, Sumardi; Juwita, Aulia Hapsari; Sari, Vita Kartika; Daerobi, Akhmad (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
This study aims to evaluate regional potential and develop strategies based on creative economy activities, both in the creative industries sector and the service sector in Wonogiri Regency. The analytical model used is qualitative method with triangulation approaches that interview from the perspectives of government, business actors, and the community. The results of the study show that five creative industry groups can represent the creative economy in Wonogiri Regency, two of which are the fashion industry (batik) and traditional food (raw cashews, soybeans, and cassava). Another sub-sector supporting the creative economy in Wonogiri Regency is tourism potential. The novelty of this research is the use of a comprehensive triangulation approach to identify creative economy sectors with untapped potential and to produce a mapping of the creative economy ecosystem specific to the characteristics of Wonogiri Regency. Currently, Wonogiri Regency has not issued legislation as a reference for creative economy development. The potential of natural resources, diversity of arts and culture, innovative and creative resources in the form of characteristics from the perspective of the creative economy, as well as infrastructure and facilities are needed to empower these potential resources. The contribution of this research is evidence-based concrete recommendations for immediately forming a Creative Economy Development Coordination Team along with infrastructure, facilities, and funding support to implement creative economy development in Wonogiri Regency.